Manifestatie in de Expo-hal tgv. 10 jaar wereldwinkels: 'Maak een begin met echte ontwikkelingshulp'. Serie van 3 foto's - Stegeman, Jan,
Manifestatie in de Expo-hal tgv. 10 jaar wereldwinkels: 'Maak een begin met echte ontwikkelingshulp'. Serie van 3 foto's.